In vitro vascularization of a combined system based on a 3D printing technique. (8th January 2014) - Zhao, Xinru; Liu, Libiao; Wang, Jiayin; Xu, Yufan; Zhang, Weiming; Khang, Gilson; Wang, Xiaohong
Abstract: A vital challenge in complex organ manufacturing is to vascularize large combined tissues. The aim of this study is to vascularize in vitro an adipose‐derived stem cell (ADSC)/fibrin/collagen incorporated three‐dimensional (3D) poly(d, l ‐lactic‐co‐glycolic acid) (PLGA) scaffold (10 × 10 × 10 mm 3 ) with interconnected channels. A low‐temperature 3D printing technique was employed to build the PLGA scaffold. A step‐by‐step cocktail procedure was designed to engage or steer the ADSCs in the PLGA channels towards both endothelial and smooth muscle cell lineages. The combined system had sufficient mechanical properties to support the cell/fibrin/collagen hydrogel inside the predefined PLGA channels. The ADSCs encapsulated in the fibrin/collagen hydrogel differentiated to endothelial and smooth muscle cell lineage, respectively, corresponding to their respective locations in the construct and formed vascular‐like structures. This technique allows in vitro vascularization of the predefined PLGA channels and provides a choice for complex organ manufacture. Copyright © 2014 John Wiley & Sons, Ltd.